2020
DOI: 10.1002/anie.202010449
|View full text |Cite
|
Sign up to set email alerts
|

Potential‐Dependent Morphology of Copper Catalysts During CO2 Electroreduction Revealed by In Situ Atomic Force Microscopy

Abstract: Electrochemical AFM is a powerful tool for the real‐space characterization of catalysts under realistic electrochemical CO2 reduction (CO2RR) conditions. The evolution of structural features ranging from the micrometer to the atomic scale could be resolved during CO2RR. Using Cu(100) as model surface, distinct nanoscale surface morphologies and their potential‐dependent transformations from granular to smoothly curved mound‐pit surfaces or structures with rectangular terraces are revealed during CO2RR in 0.1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
155
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(196 citation statements)
references
References 103 publications
(77 reference statements)
10
155
1
1
Order By: Relevance
“…This reveals that C−C coupling of CO intermediates are facilitated on the roughened anodized Cu‐MP surface. [ 3a , 3b , 16 ] This is in line with the improved SERS enhancement after anodization, suggesting that surface “hotspots” for SERS enhancement and active sites for CO coupling are simultaneously created during nanoparticle formation.…”
Section: Resultssupporting
confidence: 60%
“…This reveals that C−C coupling of CO intermediates are facilitated on the roughened anodized Cu‐MP surface. [ 3a , 3b , 16 ] This is in line with the improved SERS enhancement after anodization, suggesting that surface “hotspots” for SERS enhancement and active sites for CO coupling are simultaneously created during nanoparticle formation.…”
Section: Resultssupporting
confidence: 60%
“…Up to date, there have been different approaches to understand and reveal the process of the reconstruction and degradation mechanisms of nanostructured copper-based catalysts under ERC relevant conditions. [7][8][9]11,[15][16][17][18] Despite the multidisciplinary approaches that were employed to study Cu-based catalysts' reconstruction under ERC conditions, either through exsitu [7,16,18] and in-situ or operando [11,17,19,20] methods, there is still an active debate in the community regarding their actual mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, theoretical calculations focused on pristine atomically ordered surfaces [24] that may not be suitable for the description of the more structurally and chemically complex real‐world systems. For instance, in situ and operando spectroscopic and scanning probe microscopy studies showed that facetted surfaces change significantly under CO 2 RR conditions [26, 27, 29, 32–34] …”
Section: Introductionmentioning
confidence: 99%
“…Although significant scientific effort has been dedicated to the understanding of the active motifs and sites in CO 2 RR over Cu surfaces in order to tune their selectivity towards valuable hydrocarbons and fuels, numerous open questions still remain [23, 24, 26, 32, 35] . So far, mechanistic understanding has come from theoretical studies which still have numerous challenges to overcome in order to mimic realistic electrochemical reaction conditions.…”
Section: Introductionmentioning
confidence: 99%